2014
DOI: 10.1088/1612-2011/11/3/036003
|View full text |Cite
|
Sign up to set email alerts
|

Efficient x-ray line production from laser excited CF2Cl2clusters. Mixed cluster formation and control of the x-ray line yield

Abstract: We report on effective x-ray generation under excitation of clusters of polyatomic CF 2 Cl 2 molecules by femtosecond laser radiation of moderate intensity I ≈ 5 × 10 15 W cm −2 (E ≈ 5 mJ). The maximal laser energy conversion efficiency to chlorine x-ray lines (E = 2.6-2.8 keV) reached 2 × 10 −5 when the CF 2 Cl 2 clusters were formed in the presence of the carrier gas helium. It was demonstrated that the spectrum of laser-induced x-rays can be used to detect mixed clusters, appearing in a 3% mixture of CF 2 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The efficiency raised up to 7 · 10 −6 in the case when transform-limited laser pulse (τ ≈ 50 fs, E ≈ 25 mJ) was applied. The measured estimated X-ray generation efficiency was the same order with an efficiency obtained in our previous experiments that were carried out with argon clusters excited by the laser pulse with the energy of about 5 mJ focused at a distance of 2 mm from the nozzle outlet [16], [17]. We suppose that in the present experiment, the same efficiency was obtained due to the larger distance between the interaction zone and the nozzle outlet, i.e., smaller cluster size was compensated by the larger laser pulse energy.…”
Section: A Single-color Excitation Regimesupporting
confidence: 75%
See 1 more Smart Citation
“…The efficiency raised up to 7 · 10 −6 in the case when transform-limited laser pulse (τ ≈ 50 fs, E ≈ 25 mJ) was applied. The measured estimated X-ray generation efficiency was the same order with an efficiency obtained in our previous experiments that were carried out with argon clusters excited by the laser pulse with the energy of about 5 mJ focused at a distance of 2 mm from the nozzle outlet [16], [17]. We suppose that in the present experiment, the same efficiency was obtained due to the larger distance between the interaction zone and the nozzle outlet, i.e., smaller cluster size was compensated by the larger laser pulse energy.…”
Section: A Single-color Excitation Regimesupporting
confidence: 75%
“…One of the most exciting effects that was observed in cluster matter was the emission of powerful X-ray pulse [3], [4], [16], [17]. Later this effect was phenomenologically explained in [18] and [19] using the following arguments.…”
mentioning
confidence: 99%
“…corresponding line in x-ray spectrum. Previously, we demonstrated that mixed CF 2 Cl 2 -Ar clusters can be detected by the chlorine and argon lines in x-ray spectrum [11].…”
Section: Laser Physics Lettersmentioning
confidence: 92%
“…Femtosecond laser excitation of mixed Ar/Kr clusters: peculiarities of K-line x-ray production from nanoplasma under varied fraction of initial gas components I A Zhvaniya, M S Dzhidzhoev and V M Gordienko on the enhancement of laser energy absorption and due to this reason the production of high-energy ions, electrons and x-ray photons significantly increases [10]. We have previously shown that it is possible to utilize mixed clusters as a target to obtain a dual-energy ultrashort x-ray radiation induced by femtosecond laser [11], concurrently to the alternative multienergy x-ray sources, based on Compton and Thomson scattering [12] and synchrotrons [13].…”
Section: Laser Physics Lettersmentioning
confidence: 99%
“…A number of effects of interaction of laser radiation with polyatomic molecules have been recently studied, both experimantally and theoretically. For instance, one can mention laser-driven synthesis of chemical products [1,2], laser control of molecular electron motion [3,4], control of optical properties of a gas of coherently spinning molecules [5][6][7][8], laser-induced pyrolysis of a monosilane and boron trichloride [9], x-ray generation under interaction of femtosecond laser pulses with clusters of polyatomic molecules [10], SF − 6 anion observation [11,12] and F − (NF 3 ) n double detachment [13].…”
mentioning
confidence: 99%